PENGEMBANGAN PEMBELAJARAN LEMPAR LEMBING MENGGUNAKAN MEDIA ROKET - BUNTARAN SERAH (LP3M STKIP Muhammadiyah Muara Bungo, 2020)
One of the problems with the underdevelopment of the physical education learning process in schools, among others, is the limited learning facilities and infrastructure available in schools, lack of funds to organize programs that will produce meaningful changes, expected learning outcomes. This type of research is development research which refers to the development model of Suharsimi Arikunto. (1) conducting product analysis that will be developed from the results of field observations and literature reviews, (2) developing the initial product form, (3) expert evaluation using one physical education expert and one junior high school physical education learning expert, and small-scale trials (10 students ), using a questionnaire and then analyzed, (4) initial product revisions, (5) large-scale trials (32 students), (6) final product revisions after conducting large-scale field trials, (7) final results of rocket media for students Class XI SMK produced through revision of large-scale field trials. The instrument used was a questionnaire questionnaire. The data analysis technique is a descriptive percentage. The conclusion of this study is the results of the assessment of the experts, namely, Physical Education experts 92% (very good) and learning experts 98% (very good). Student cognitive learning outcomes of ≥ 88%.